Optimal Cooling Systems in Current Data Centers (Global Journal of Computer Science and Technology, 2025)
echnological advancement has shown a vital impact in current world trends It has enabled communication information processing and collaboration among various aspects from personal use to departmental collaborations in workplace organisation Therefore it is important to understand the concepts of Information Technology IT infrastructure taking roles in evolving for the landscape of adaptability of information technology for the ever-changing demandson organisational needs IT infrastructure components such as the hardware software and the operating systems requires to have well designed IT infrastructure enhancing productivity security and accessibility Hence adapting to technological demands and changes with innovation 1